2018
DOI: 10.2147/amep.s160701
|View full text |Cite
|
Sign up to set email alerts
|

Fourth-year medical students do not perform a focused physical examination during a case-based simulation scenario

Abstract: BackgroundThe art of physical examination is one of the most valuable diagnostic tools bestowed upon new generations of medical students. Despite traditional educational techniques and significant attention on a national level, both trainees and educators have noticed a decrease in physical examination proficiency. Simulation has been identified as a potential way to improve physical examination techniques within undergraduate medical education. We sought to determine the utility of a cardiac case-based simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…This theme was constructed from two observational studies and describes how technology leads to disjunctions between education and practice [ 8 56 ]. These observations suggested misalignments between learning and practice, pointing out insufficient engagement between both touch and technology, although the studies had very different findings.…”
Section: Resultsmentioning
confidence: 99%
“…This theme was constructed from two observational studies and describes how technology leads to disjunctions between education and practice [ 8 56 ]. These observations suggested misalignments between learning and practice, pointing out insufficient engagement between both touch and technology, although the studies had very different findings.…”
Section: Resultsmentioning
confidence: 99%
“…A result similar to the percentage of correct answers for the cardiopulmonary monitoring skill was found in a study carried out at the Faculty of Medicine of Ribeirão Preto, in which 83% of candidates for medical residency requested electrocardiographic monitoring during the assess- (14) . On the other hand, research carried out at the Beth Israel Deaconess Medical Center pointed out that fourth-year medical students did not adequately perform the patient's anamnesis, demonstrating limited performance in the physical examination during a simulation of chest pain with a high-fidelity mannequin (15) . The "immediate treatment" competency encompasses skills such as oxygen therapy and medication administration according to the protocol (8) , in which the students had high percentages of correct answers from 96.7% to 100%, demonstrating decision-making and attitude when performing properly.…”
Section: Discussionmentioning
confidence: 99%
“…In general, acquiring heart auscultation skills are a difficult task. The gradual deterioration of the quality of education is caused by: time limits, low availability of thematic patients, the severity of the patient's condition, the presence of psychological problems in students when working with a real patient, the direct refusal of patients to communicate with students [15].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, weak cardiological examination skills were recorded in medical students using cardiac simulators [7], [8], computer training programs [9], and at the patient's bedside [10], [11]. In several well-planned randomized trials, no significant differences were found between heart simulations and other interventions [12], [13], [14], [15]. Thus, it remains unclear whether there is any intervention that can be applied at an early stage of medical training, contributing to the improvement of heart auscultation skills.…”
Section: Introductionmentioning
confidence: 99%